Portraits of Protest in Florida: How Opt-Out Makes the Personal Political. Issue 5 (May 2021) - Currin, Elizabeth; Schroeder, Stephanie; Mccardle, Todd
Background/Context: Opting out of high-stakes standardized tests, a phenomenon so widespread in the United States as to be regarded as a movement, is nevertheless a misunderstood and often maligned force in educational politics. Purpose: This article offers a counternarrative of opt-out activism—a more thorough and vivid account of what we view as an unfairly maligned movement with tremendous potential for improving and preserving our nation's schools. Participants: In-depth portraits introduce three members of the Opt Out Florida Network: Cindy Hamilton, an unabashed leader whose children have graduated; Sandy Stenoff, her partner in protest whose children remain in the system; and Susan Bowles, who grapples with conflicting roles of pedagogue and protester. Research Design: As a critical ethnography, this study uses a qualitative approach to expose and challenge the unjust treatment of the opt-out movement, guided by the following research questions: 1) How do opt-out activists understand and explain their journeys to activism? 2) What experiences, concerns, and commitments guide them in their daily fight against high-stakes standardized testing? Data Collection and Analysis: Using transcript data from focus group and 1-on-1 follow-up phone interviews, the research team composed and analyzed narrative portraits, which offer models of resistance to neoliberal education reform. Conclusions: Contrary to their portrayal as passive, anti-test, anti-accountability parents solely focused on their own children, the opt-out movement is an active community of highly informed individuals dedicated to effecting positive change in education. The nuance of narrative captures the messy realities of activism, illustrating how parents and teachers must work together, guided by a view of citizenship as shared fate, to fight for more equitable and educative schools.